2018
DOI: 10.3122/jabfm.2018.06.180166
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Hypertension Control Across and Within Three Health Systems Participating in a Data-Sharing Collaborative

Abstract: Introduction: We aimed to standardize data collection from 3 health systems (HS1, HS2, HS3) participating in the San Francisco Bay Collaborative Research Network, and compare rates and predictors of uncontrolled blood pressure among hypertensive adults to identify opportunities for regional collaboration in quality improvement. Methods: Retrospective cohort study using deidentified electronic health record data from all primary care patients with at least 1 visit in a 2-year period, using standard data defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The articles in this 2018 JABFM theme issue highlight that practice-based research is alive and well; however, we are concerned about the state of PBRNs. In this issue, only 4 articles report PBRN research 23,25,40,42 and the others report non-PBRN practice-based research. So, how important are PBRNs to practice-based research?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles in this 2018 JABFM theme issue highlight that practice-based research is alive and well; however, we are concerned about the state of PBRNs. In this issue, only 4 articles report PBRN research 23,25,40,42 and the others report non-PBRN practice-based research. So, how important are PBRNs to practice-based research?…”
Section: Resultsmentioning
confidence: 99%
“…Obtaining analyzable data from different EMRs is a huge barrier, especially if there are different vendors, but it remains a priority with PBRNs. Selby et al 40 were able to compare hypertension control data by using a common data repository from 3 different health systems with 2 different EMRs, a laudable accomplishment. They compared risk for uncontrolled hypertension between and within health systems, which can inform future QI interventions.…”
Section: Community Population and Public Health Engagementmentioning
confidence: 99%
“…Site-specific characteristics, such as the inclination to intensify medication, were related to the site’s levels of BP control. An analysis of 3 health systems participating in the San Francisco Bay Collaborative Research found the percentage of patients in control varied by as much as 32% across sites 30. A study in Great Britain identified that smaller practice size was associated with uncontrolled BP; however, much of the variation was uncharacterized 31.…”
Section: Discussionmentioning
confidence: 99%
“…Further details on our methods to define our research cohorts and extract/clean/link data from the EHR data can be found in an earlier publication. 25 The Institutional Review Board approved the study at the University of California, San Francisco, with a waiver for informed consent.…”
Section: Discussionmentioning
confidence: 99%